New structure of sliding mode control for variable speed wind turbine. (December 2020) - Berrada, Youssef; Boumhidi, Ismail
Abstract: This article investigates a new sliding mode control structure for a variable speed wind turbine, in order to maximize the captured wind energy and to reduce the transient loads (shafts vibration) caused by the fast fluctuation of wind speed. The variable speed wind turbine control presents a difficult problem because of the nonlinearities of equivalent mathematical models and the effects of external disturbances (wind speed fluctuation). The sliding mode technique is a nonlinear control, widely used in this field; this is due to its robustness in terms of stability and performance against disturbances and modeling uncertainties, and its simplicity of implementation. However, this technique has a major problem which is the chattering phenomenon caused by the discontinuous portion of its control law. A new structure of sliding mode technique is developed in this paper to overcome this phenomenon and maintain the effectiveness of traditional approach. The performance of the developed control will be offered by numerical simulations and will be compared to the basic method of sliding mode control based on a strong nonlinear model of wind turbine.